Upaya Guru dalam Menanamkan Sikap Religius Pembelajaran Agama Islam pada Masa Pandemi Covid-19 - Rifdah Fauziah; Ina Magdalena; Romi Ramdon Ginanjar; Candra Puspita Rini; Dayu Retno Puspita (Journal on Education, 2023)
The purpose of this study is to describe the teacher’s efforts in instilling a religious attitude in Islamic learning during the covid-19 pandemic and to describe the problems faced in Islamic learning during the covid-19 pandemic. This research was conducted at MIN 1 Tangerang which is located on Jl. Bitung Cisereh Rt003/003, Kadu Jaya Village, Curug District, Tangerang-Banten Regency. This research method uese descriptive qualititative method. While the data collection techniques in the form of observation, interviews and documentation. In instilling religious attitudes, there are aspects of religious values, namely the value of worship, the value of trust and sincerity, the value of morals and discipline, and the value of exemplary. From the result of this study, aspects of the value of worship are sunnah and fardhu prayers, tadarus al-qur’an, istighosah, reading prayers before and before learning, and reading surat al’ashr. The values of rauhul jihad are helping, helping Islamic holidays, and muhadoroh. The values of amanah and ikhlas are charity, responsibility, and please help. Moral and discipline value are 5 S (Smile, Greetings, Greetings, Polite and Courteous), comply with health protocols, and are good. The problems faced by teachers in Islamic religious learning are the lack of teacher knowledge on the use of sosial media less objective assessment, and teh influence of the outside environment on students.